The problem of location selection during the order-pickingprocess - Tarczyński, Grzegorz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper treats the problem of optimizing the order-picking process in multi locations of the same item. The issue concerns multi-criteria decision- making. The main goals that can be achieved in this situation are the minimization of average order-picking time and the maximization of the number of locations totally cleared. In the paper, the proposed simple heuristic that minimizes the number of picking-aisles visited by the picker is compared using the Dmytrów’s TMAL method. The results are evaluated by the following criteria: the average distance covered by the picker, the average order-picking time, priority ratio and the number of locations totally cleared. The manual system and one-block rectangular warehouses with two popular routing heuristics, return and S-shape, are considered in the analysis. The research was carried out using simulations.
Mathematical Economics; 2017; Nr 13 (20); s. 79-93
Keywords: decision trees; logistic regression; turnover intention